Knowledge and attitudes on induced abortion in adolescents 5th year of high School - Trujillo Mamani, Grover Eyden (2016)
The object of this study is to determine the relation between knowledge and attitude about induced abortion in 5th year high school teen. The research design is not experimental with a cross-sectional, correlational type. A stratified probability sampling was conducted, determining a sample of 128 students enrolled in the academic year of 2015. The instrument used is the questionnaire of knowledge about induced abortion consisting of 14 questions and the scale of attitudes about induced abortion consisting of 18 items with a response in the Likert scale, it has a duration of 15 minutes. The results indicate that 53.9% of students have an average level of knowledge about induced abortion and just 22.7% have a high level; in relation to the attitudes 43.0% of students present an attitude of acceptance for induced abortion and 21.9% present and attitude of rejection for abortion. A significant correlation was found between the study variables (sig = .000). Conclusions: the higher the knowledge, the higher the attitude of rejection for induced abortion; the lower the level of knowledge, the higher the attitude of acceptance for induced abortion